2014
DOI: 10.1186/1471-2164-15-67
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated evolution of the mitochondrial genome in an alloplasmic line of durum wheat

Abstract: BackgroundWheat is an excellent plant species for nuclear mitochondrial interaction studies due to availability of large collection of alloplasmic lines. These lines exhibit different vegetative and physiological properties than their parents. To investigate the level of sequence changes introduced into the mitochondrial genome under the alloplasmic condition, three mitochondrial genomes of the Triticum-Aegilops species were sequenced: 1) durum alloplasmic line with the Ae. longissima cytoplasm that carries th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 58 publications
(95 reference statements)
0
14
0
1
Order By: Relevance
“…Molecular analyses are only beginning to address the functional implications of the alloplasmic condition. For instance, comparative analysis of the mitochondrial genomes among a wheat alloplasmic line and its two parents indicated accelerated evolution of the mtDNA under the alloplasmic condition resulting in SNP variation and structural rearrangements (NOYSZEWSKI et al 2014). Detailed analysis of one particular mitochondrial gene essential to ATP production, ATP synthase subunit 6 (ATP6), revealed moderate SNP variation, but much more substantial structural and presence/absence variation across the Triticum-Aegilops complex, suggesting rearrangements as the predominate evolutionary driving force in the mitochondria (SOLTANI et al 2014).…”
Section: Cybrid Plants and Alloplasmic Linesmentioning
confidence: 99%
“…Molecular analyses are only beginning to address the functional implications of the alloplasmic condition. For instance, comparative analysis of the mitochondrial genomes among a wheat alloplasmic line and its two parents indicated accelerated evolution of the mtDNA under the alloplasmic condition resulting in SNP variation and structural rearrangements (NOYSZEWSKI et al 2014). Detailed analysis of one particular mitochondrial gene essential to ATP production, ATP synthase subunit 6 (ATP6), revealed moderate SNP variation, but much more substantial structural and presence/absence variation across the Triticum-Aegilops complex, suggesting rearrangements as the predominate evolutionary driving force in the mitochondria (SOLTANI et al 2014).…”
Section: Cybrid Plants and Alloplasmic Linesmentioning
confidence: 99%
“…CMS often develops when the cytoplasm, donated by wild relative, is incompatible with cultivar-derived nucleus, and the specific Rf gene is located within the genome of the wild relative. These types of alloplasmic lines often retain mitochondrial segments derived from the wild donor, also defined as mitotype-specific sequences (MSSs) [50], and is most often observed in wheat [51, 52] and Brassicas [5355].…”
Section: Introductionmentioning
confidence: 99%
“…1). In silico translation revealed that ATP6-1a encodes a 386 amino acid (aa) polypeptide with a high degree of similarity to the ATP6-1 protein present in T. aestivum (Ogihara et al 2005) and T. turgidum mitochondrion (Noyszewski et al 2014). The ATP6-1b encodes a 415 aa protein, which is identical to a previously reported gene in Ae.…”
Section: Atp6-1 Diversity In the Triticum-aegilops Complexmentioning
confidence: 99%